2006
DOI: 10.1037/0022-3514.91.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The Single Category Implicit Association Test as a measure of implicit social cognition.

Abstract: The Single Category Implicit Association Test (SC-IAT) is a modification of the Implicit Association Test that measures the strength of evaluative associations with a single attitude object. Across 3 different attitude domains--soda brand preferences, self-esteem, and racial attitudes--the authors found evidence that the SC-IAT is internally consistent and makes unique contributions in the ability to understand implicit social cognition. In a 4th study, the authors investigated the susceptibility of the SC-IAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
1,093
3
17

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 947 publications
(1,136 citation statements)
references
References 40 publications
23
1,093
3
17
Order By: Relevance
“…Another issue with the implicit measures used in this design are their relative nature -changes in IAT or MC-IAT scores may reflect changes in attitudinal responses to Blacks, Whites, or both. Future investigations using implicit measures that are more adept at targeting associations for a single object (e.g., the Single-Category IAT; Karpinski & Steinman, 2006) may shed more light on the mechanisms underlying the malleability effects found in these studies. As implicit measures mature, replicating this design with new methods will increase confidence in the theoretical interpretation of what these interventions are changing.…”
Section: Limitationsmentioning
confidence: 99%
“…Another issue with the implicit measures used in this design are their relative nature -changes in IAT or MC-IAT scores may reflect changes in attitudinal responses to Blacks, Whites, or both. Future investigations using implicit measures that are more adept at targeting associations for a single object (e.g., the Single-Category IAT; Karpinski & Steinman, 2006) may shed more light on the mechanisms underlying the malleability effects found in these studies. As implicit measures mature, replicating this design with new methods will increase confidence in the theoretical interpretation of what these interventions are changing.…”
Section: Limitationsmentioning
confidence: 99%
“…Imaging techniques would also be useful in providing a more fine-grained assessment of the relative activation of the left versus the right hemisphere in the representation and processing of self-esteem (the results we report here do not rule out right hemisphere involvement -our correlational analysis indicates a relationship between the hemispheres) and in providing detail concerning anterior/posterior and cortical/subcortical involvement. Recent studies have indicated an important role for the medial prefrontal cortices in decisions related to self-referential judgements (Kelley et al, 2002;Vogeley et al, 2004;Mitchell et al, 2005) and future research could undertake to reconcile such findings with research concerning the lateralisation of emotion and self-esteem. Finally, replications of our results with non-linguistic stimuli (perhaps utilising presentation of Picture IAT stimuli to alternate visual hemifields) would be valuable.…”
Section: ______________________________mentioning
confidence: 99%
“…An inherent limitation of this standard version is that it cannot reveal participants' evaluative associations with a single target concept (Karpinski and Steinman, 2006).…”
Section: ______________________________mentioning
confidence: 99%
See 2 more Smart Citations